Application of a modified healing cap in implant supported auricular prosthesis: case report - Arzu Atay; Cihan Gürbüz; Simel Ayyıldız; Yumuşhan Günay (Cumhuriyet Dental Journal, 2014)
Auricular prosthesis are fabricated generally in congenital deformities or tissue deficiencies gained by a trauma. Due to the difficulty of prosthetic localization, implant supported auricular prosthesis have important mechanical advantages when compared to those used with tissue adhesives. However, during the prosthetic preparation period of post implantation stage, problems like thickening of the skin tissue around the healing caps may be seen. This condition often requires a third surgical procedure for remodification of the healing tissues. This case report presents the application of modified healing cap which was attached to the prosthetic part of the patient which could not be rehabiliated due to the thickening of the tissue .